1984
DOI: 10.1037/0735-7044.98.3.405
|View full text |Cite
|
Sign up to set email alerts
|

Posterodorsal septal lesions impair performance on both shift and stay working memory tasks.

Abstract: Two groups of rats were trained preoperatively on either a shift or a stay problem in a T-maze. Training trials consisted of two runs, an "information run" in which a subject was forced to go down one of the two arms of the T-maze, followed immediately by a "choice run" in which the subject could choose either arm. In the shift condition, rats were rewarded with wet mash only for choosing the arm opposite the one they entered on the information run. In the stay condition, rats were rewarded for entering the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 34 publications
4
41
1
Order By: Relevance
“…However, the accuracy rate was not correlated with an increase in the concentration of GABA. Stanton et al (26) showed that posterodorsal septal lesions impair behavioral functions, resulting in a decrease in the accuracy rate in both the delayed matching to sample (DMTS) and delayed non-matching to sample (DNMTS) tests. Furthermore, declines in the accuracy rate in the DNMTS task in T-maze test have been reported in relation to lesions in the inside septum (27), outside septum (28), entorhinal cortex (29), and the CA3 region of the hippocampus (30,31).…”
Section: Resultsmentioning
confidence: 99%
“…However, the accuracy rate was not correlated with an increase in the concentration of GABA. Stanton et al (26) showed that posterodorsal septal lesions impair behavioral functions, resulting in a decrease in the accuracy rate in both the delayed matching to sample (DMTS) and delayed non-matching to sample (DNMTS) tests. Furthermore, declines in the accuracy rate in the DNMTS task in T-maze test have been reported in relation to lesions in the inside septum (27), outside septum (28), entorhinal cortex (29), and the CA3 region of the hippocampus (30,31).…”
Section: Resultsmentioning
confidence: 99%
“…Delayed matching to sample procedure (DMTS) is frequently used for studying short-term memory or working memory (1,2). In the rat experiment, there are usually two selections (right side or left side), so the chance level is high (50%).…”
mentioning
confidence: 99%
“…Also, when given a choice, they typically enter a novel, previously unavailable alley rather than an alley in which they have been repeatedly reinforced (Means et al, 1974). Furthermore, in a study comparing acquisition of win-stay and win-shift responses during pairs of trials in aT-maze in which the animal was forced to a randomly selected goal box on the first trial and given a choice on the second trial, it was demonstrated that rats are capable of acquiring either response, but that it takes fewer trials to acquire the win-shift response (Stanton, Thomas, & Brito, 1984). Also, in the radial-arm maze rats spontaneously enter novel (unentered) alleys and more readily learn to enter previously unentered arms (win-shift) than to return to arms that have already been entered (win-stay), even if each arm is baited with food or water before all trials (Gaffan & Davies, 1981;Olton & Schlosberg, 1978).…”
mentioning
confidence: 99%